Efficient and Effective Management of Organizations Require Appropriate Ethical Relations Between Stockholders and Stakeholders. An Evaluation of the Morality (Ethics) between Stockholders and Stakeholders on the Organization and their Relationship with Employees - Kwadade-Cudjoe, Francis (Advances in Social Sciences Research Journal, 2022)
Peaceful co-existence of stockholders and stakeholders, comprising customers, consumers, employees, managers, suppliers/vendors, shareholders, etc. has always been problematic for organizations to thrive. Stockholders and owners of entities normally invest a lot of money into business with the sole aim of recouping their funds, and with interest. However, managers and employees also accept to work in organizations with the aim of earning good emolument to be able to live and survive. For the organization to be able to achieve competitive advantage, there should be understanding by employees to work hard and co-operate with stockholders by observing the laid down rules, and the owners equally providing good working conditions. This would enable managers and employees to give their best for the success and sustenance of the organization. Unfortunately, the globe is experiencing hard times due to the upsurge of Covid-19 which affected development and destroyed lot of lives, and currently the Russia and Ukraine war, which has also exacerbated the situation and escalated prices of goods. Both stockholders and stakeholders have the moral rights to co-exist peacefully for the success of organizations, which would benefit all parties.